Safety and feasibility of hybrid tracheostomy - Daeun Kang; In Beom Jeong; Sun Jung Kwon; Ji Woong Son; Gwan Woo Ku (Acute and Critical Care, 2021)
Background Percutaneous dilatational tracheostomy (PDT) is widely used in intensive care units, but this conventional method has some disadvantages, such as requirement of a lot of equipment and experts at the site. Especially, in situations where the patient is isolated due to an infectious disease, difficulties in using the equipment may occur, and the number of exposed persons may increase. In this paper, we introduce hybrid tracheostomy that combines the advantages of surgical tracheostomy and PDT and describe our experiences. Methods Data from 55 patients who received hybrid tracheostomy without bronchoscopy from January 2020 to February 2021 were collected and reviewed retrospectively. Hybrid tracheostomy was performed at the bedside by a single thoracic surgeon. The hybrid tracheostomy method was as follows: after the skin was incised and the trachea was exposed, only the extent of the endotracheal tube that could not be removed was withdrawn, and then tracheostomy was performed by the Seldinger method using a PDT kit. Results The average age was 66.5 years, and the proportion of men was 69.1%. Among the patients, 21.8% were taking antiplatelet drugs and 14.5% were taking anticoagulants. The average duration of the procedure was 13.3 minutes. There was no major bleeding, and there was one case of paratracheal placement of the tracheostomy tube. Conclusions In most patients, the procedure can be safely performed without any major complications. However, patients with a short neck, a neck burn or patients who have received radiation therapy to the neck should be treated with conventional methods.